Mnemosine Laranjeiras : glossário ilustrado de 1908 - Vilas-Bôas, Loíze Raquel Santos Silva (2022)
Laranjeiras is a city in Sergipe that houses a rich cultural heritage resulting from its historical legacy, and its municipal archive has the custody of documents that recorded the dynamics of the city over the centuries. This work is justified, in the first place, by the importance of heritage education for the popular awareness of the preservation of public cultural assets, in addition to the rescue of the documentary history of the municipality, which can provide further research through documentary sources found in the city's archive. This dissertation had as main objective the elaboration of an illustrated glossary focusing on the year 1908 for a varied target audience, which will be able to know the material after its publication. For the making of the glossary, 63 entries were filtered that were in the Book of Laws, Decrees, Records and Resolutions of the Municipal Council of Laranjeiras from the collection of old bound documents of the Municipal Public Archive of the city. For the selection of entries, archaisms, regionalisms, terms that had their spelling changed, terms little known or from specific areas were considered. The illustrated glossary can be used as a reference guide regarding the city's curiosities and that can arouse interest in research in different areas based on novelties observed in the work. In addition to the exposed elements, it can also be said that the “Mnemosine Laranjeiras” can be a Heritage Education activity, as it prioritizes the singularities of the region, valuing the cultural assets of the city. It is also believed that the illustrated glossary can be useful to promote a better understanding of the documents and the society of Laranjeiras, and by extension Sergipe of the beginning of the 20th century. Thus, it is recommended that other works of this nature be carried out with the different books of the Old Documents Fund of the Municipal Archive of Laranjeiras.